PENANGGULANGAN TINDAK PIDANA PENYELUNDUPAN MELALUI JALUR UDARA OLEH DIREKTORAT JENDERAL BEA DAN CUKAI – BANDARA NGURAH RAI - BALI - Elviani Ndun, Helsi; Rai Setiabudhi, I Ketut; Parwata, I Gusti Ngurah (Kertha Wicara : Journal Ilmu Hukum; Vol. 04, No. 01, Februari 2015)
The title of this paper is “ The Prevention the Crime of Smuggling through Air byDirectorate General of Customs and Excise - NgurahRai airport - Bali. DirectorateGeneral of customs and Excise or Customs, served as the traffic surveillance system forexport import goods in Indonesia in order to prevent the crime of smuggling, especiallyfor goods that distribute through air line and will be handled in NgurahRai airport inBali. The first problem occur is how the efforts of Directorate General of customs andExcise in terms of solving the criminal acts of smuggling through the air line ; second,which factors that impeding duty and authorities implementation by DirectorateGeneral of customs and Excise in eradicating the criminal acts of smuggling. This typeof research is empirical, which uses the techniques of data collection which is throughinterview. The criminal acts of smuggling is one crime that is detrimental to society andthe State in the field of export import. Therefore, the Customs has an important role intackling and eradicating the criminal acts of smuggling through direct inspection for export-import goods. The Customs has legal arrangements against crime of smugglingand offences that are provided for in Act No. 17 of 2006 about customs. The conclusionof this research shows that the crime acts of smuggling is still happen due to someinhibitory such as the human resources that still inadequate. Therefore, the supervisionon criminal acts of smuggling still weak.
Keywords: Customs, the criminal acts of smuggling, import export goods